Preparation and Characterization of Transition Metal Complexes of 4-Oximino-1(2’,4’-dinitrophenyl)-3-Methyl-2-Pyrazolin-5-One - J. Kharodawala, Mohammad; K. Rana, Arjun (Asian Journal of Chemistry, 2010)
Oxovanadium(IV), chromium(III), managanese(II), iron(III), cobalt(II), nickel(II), copper(II) and zinc(II) complexes of 4-oxinino- 1-(2'.4' -dinitrophenyl)-3-methyl-2-pyrazolin-5-one have been prepared and cbalacterized on the basis of elemental analysis. conductivity, magnetic moment and spectral studies. All complexes except chromium(III) and iron(III) having general composition M(ODMPZ)2·2H2O while the chrotnium(III) and iron(III) complexes are M(ODMPZ)3 . The ligand field parameters for VO(II), Cr(III), Ni(II) and Co(II) chelates are also calculated.